Dampak Pajak Ekspor Minyak Sawit Terhadap Permintaan Minyak Goreng Sawit (Crude Palm Oil) Dan Minyak Goreng Kelapa (Crude Coconut Oil) Indonesia - Purba, Jan Horas Veriyadi (Jurnal Ilmiah Ranggagading (JIR), 2010)
Indonesia is the biggest palm oil producer and exporter in the world. In 2008, Indonesia contributed 34.3% of total palm oil world production and 84.6% of production was exported as crude palm oil (CPO). In the world market, the growth of palm oil consumption and import were 9.66%/year and .34%/year. In supply side, palm oil production and export increased 7.94%/year and 9.55%/year respectively. It reflected global excess demand which influence palm oil price in world market, 1.69%/year. This situation caused act toward an export tax regulation on palm oil in order to ensure the availability of palm oil to fulfill national necessity. By using annual data 1979-2008 periods, an econometric approach was applied in this study. The goal of this study is to analyze (a) the performance of Indonesia palm oil, such as oil palm harvested area, palm oil production and palm oil export, (b) the international trade of palm oil in selected countries, (Malaysiaâs palm oil export, and also India and Chinaâs palm oil import; (c) price integration; (d) the influence of oil price toward world CPO demand. The findings of the study show that (a) the world palm oil price is not significant determinants of Indonesia palm oil export. Import demand of India and China have been found to play an important role in shaping Indonesia palm oil export; (b) there was the price integration between the world and the domestic palm oil prices, and (c) world petroleum prices also proved to be important factors affecting the demand of world palm oil for biodiesel. Keywords: crude palm oil (CPO), export tax, biodiesel, oil price